1971
DOI: 10.1111/j.1537-2995.1971.tb04416.x
|View full text |Cite
|
Sign up to set email alerts
|

An Antibody, in the Serum of a Wr(a+) Individual, Reacting with an Antigen of Very High Frequency

Abstract: The serum of a Wr(a+) woman has becn found to contain an antibody reacting with an antigen of very high incidence. Preliminary tests on the rtrcngth of the Wra antigen on the cella of the antibody forma and the variation of reactions of the antibody with the cells of nonrelated Wr(a+) and Wr(a-) individuals suggest that the antibody may be detecting the antithetical antigen to Wra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

1986
1986
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(14 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…Positions of the amino acid substitutions associated with the Diego system antigens are shown. The name anti -Wr b was provisionally used in 1971 for an antibody, in the serum of a Wr(a + ) woman, that detected a high frequency antigen [6] . The large cytoplasmic N -terminal domain is not shown.…”
Section: Anti-di a And -Di Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Positions of the amino acid substitutions associated with the Diego system antigens are shown. The name anti -Wr b was provisionally used in 1971 for an antibody, in the serum of a Wr(a + ) woman, that detected a high frequency antigen [6] . The large cytoplasmic N -terminal domain is not shown.…”
Section: Anti-di a And -Di Bmentioning
confidence: 99%
“…Alloanti -Wr b has been found in the sera of the three Wr(a + b -) patients [6,99,100] , plus some Wr(a -b -) individuals with certain rare MNS phenotypes (Sections 3.5 and 3.10). Wr b is generally considered resistant to treatment of red cells with proteases, but one anti -Wr b did not react with fi cin -or papain -treated red cells [100] .…”
Section: Anti-wr Bmentioning
confidence: 99%
“…Data obtained with Wr(a+b+) membranes from donor S.Z 5. Data obtained with Wr(a-b+) and Wr(a+b+) membranes were similar 6. A^-(3-Dimethylaminopropyl)W-ethylcarbodiimide/glycine ethyl ester.…”
mentioning
confidence: 98%
“…[2], The high level of expression of Wra antigen on the red cells of this patient compared with that of her Wr(a+) relatives suggested that she might be a Wr"Wra homozygote. Family studies were inconclusive because only a few members were available for testing.…”
Section: Introductionmentioning
confidence: 99%